2020
DOI: 10.3389/fgene.2020.608517
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibroblast Growth Factor 23 With Ischemic Stroke and Its Subtypes: A Mendelian Randomization Study

Abstract: Fibroblast growth factor 23 (FGF23), which is involved in the regulation of vitamin D, is an emerging independent risk factor for cardiovascular diseases. Previous studies have demonstrated a positive association between FGF23 and stroke. In this study, we aimed to assess the association of FGF23 with ischemic stroke and its subtypes by applying a Mendelian randomization (MR) framework. Five genetic variants obtained from a genome-wide association study involving 16,624 European subjects were used as valid ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…The primary outcomes included CAD (Nikpay et al, 2015), MI (Nikpay et al, 2015), HF (Shah et al, 2020), and AF (Roselli et al, 2018). We also included cardiovascular risk factors as secondary outcomes, including blood pressure [systolic blood pressure (SBP), diastolic blood pressure (DBP) (Mitchell et al, 2019)], body mass index (BMI) (Yengo et al, 2018), glycemic traits [fasting glucose (FG)] (Lagou et al, 2021), glycated hemoglobin (HbA 1c ) (Wheeler et al, 2017), and T2DM (Mahajan et al, 2018), but not lipids and stroke because they have been thoroughly investigated in previous studies (Yokomoto-Umakoshi et al, 2020;Zheng et al, 2020). Given that FGF23 is closely related to kidney function (Robinson-Cohen et al, 2018), we also included kidney function as secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary outcomes included CAD (Nikpay et al, 2015), MI (Nikpay et al, 2015), HF (Shah et al, 2020), and AF (Roselli et al, 2018). We also included cardiovascular risk factors as secondary outcomes, including blood pressure [systolic blood pressure (SBP), diastolic blood pressure (DBP) (Mitchell et al, 2019)], body mass index (BMI) (Yengo et al, 2018), glycemic traits [fasting glucose (FG)] (Lagou et al, 2021), glycated hemoglobin (HbA 1c ) (Wheeler et al, 2017), and T2DM (Mahajan et al, 2018), but not lipids and stroke because they have been thoroughly investigated in previous studies (Yokomoto-Umakoshi et al, 2020;Zheng et al, 2020). Given that FGF23 is closely related to kidney function (Robinson-Cohen et al, 2018), we also included kidney function as secondary outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Previous MR studies have mainly focused on the associations of genetically predicted FGF23 with bone-related phenotypes, which showed that FGF23 is inversely related to bone mineral density and osteoporosis (Wang et al, 2020;Yokomoto-Umakoshi et al, 2020). Other MR studies also assessed its relation with CAD, stroke, blood pressure, and lipids (Yokomoto-Umakoshi et al, 2020;Zheng et al, 2020), but these studies have not assessed the relation with HF, AF, or type 2 diabetes mellitus (T2DM). Furthermore, since some of these previous studies were conducted in genomewide association studies (GWAS), which have differences in disease and control definition, analysis model, and study design of the included studies, or may have included potentially invalid instrument such as a highly pleiotropic single-nucleotide polymorphism (SNP) in the ABO gene (Folkersen et al, 2020;Wang et al, 2020;Yokomoto-Umakoshi et al, 2020;Zheng et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Northern Manhattan Study (NOMAS) conducted on 212 patients also reported no association of FGF23 with ischemic stroke after adjusting the risk of stroke factors (Wright et al, 2014). However, Panwar et al demonstrated that there was no significant association of FGF23 concentrations with all incident stroke, but in a prespecified analyses, only cardioembolic stroke occurred due to the high level of FGF23 (Panwar et al, 2015), which is consistent with "FGF23 association with ischemic stroke and its subtypes" study by Zheng et al (Zheng et al, 2020). Nearly two decades passed, and more randomized clinical trials of FGF in patients with acute ischemic stroke are needed (Wahlgren and Ahmed, 2004).…”
Section: Progress In Fgf Research For Clinical Stroke Treatment Therapeutic Potentialmentioning
confidence: 66%
“…Therefore, considering the relation of LVH with elevated arteriosclerosis, it could be partly explained that FGF23 has an effect on stroke risk. Also, the association of FGF23 with ischemic stroke and its subtypes has some limitations, because the methodologies used to measure the FGF23 levels could cause some biasness in the results (Zheng et al, 2020). Bioinformatics analysis of genes revealed that brain FGF9 gene expression levels are increased in stroke patients (Zou et al, 2019).…”
Section: Serum Biomarkersmentioning
confidence: 99%